Left behind radiological investigations: An inherent problem - Govindswamy, Giridhar A (Medknow Publications, 2011)
OBJECTIVES: To assess the number of investigations left behind by patients in radiology department, their cost, and the possible methods of reducing the problem. MATERIALS AND METHODS: A total of 1424 radiographs, 160 computed tomography (CT) scans, 300 ultrasonography (USG) reports, and 46 Doppler reports were left behind by patients in one financial year. The total cost of these left behind investigations was calculated and the reports were categorized into normal and abnormal for each modality. RESULTS: Of the radiographs left behind 658 were abnormal, with 211 among these being radiographs of postoperative patients. Thirty-seven percent of CT scans had positive findings. Sixty-eight percent of USG reports had positive findings while 46% of Doppler reports were abnormal. CONCLUSION: We believe that the cost and number of these left behind investigations over a period of time would definitely be significant for the health care system in a developing country. It is time to think of the possible reasons and methods for containing this problem.